The Influence of Financial Literacy on The Behavior of Civil Servants in Choosing Pension Financing in Syariah Banks - Purba, Rendi; Indra, Ahmad Perdana; Anggraini, Tuti (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
There are quite a few new entrepreneurs who are entering retirement, whose entrepreneurial decisions are motivated by many reasons, ranging from unpreparedness of pension funds, activities in old age, to the existence of business opportunities. However, funding problems are a common initial problem. Therefore, there are many ways to start a business. One of them is bank financing. This study aims to test the influence of bank financial literacy and marketing policies on pension financing decisions in Islamic banks. Data were collected through objective sampling from 30 civil servants who were interviewed. The research method used is quantitative (Informal). In testing the hypothesis, SPSS is used as a data analysis tool. The results showed that economic literacy influenced the behavior of 54.6% of civil servants, while the rest were influenced by other variables. This research contributes to the literature on financial literacy and its impact on financial decision-making within the context of Sharia banking. The results underscore the importance of enhancing financial literacy programs targeted at civil servants to improve their financial choices and promote the growth of Sharia banking products. Recommendations for policymakers and financial institutions are provided to facilitate better financial education and support for civil servants in their pension planning.